Factors Affecting Budgeting Practices of Principals In The Administration of Public Secondary Schools in Southwest Nigeria - OBIWELUOZOR, Nkechi; Ogunbiyi, Oluwadare Deji (International Journal of Islamic Business and Management Review, 2022)
The study assessed the factors affecting budgeting practices of principals in administration of public secondary schools in Southwest, Nigeria. The study was guided by one objective, research question and hypothesis. Descriptive survey research design was used for the study; the population of the study was 3254 while the sample size was 650 respondents. Multi-stage sampling technique was use to arrive at the sample size. The instrument used for data collection was a self-structured questionnaire titled “Factors Affecting Principals’ Budgeting Practices Questionnaire (FAPBPQ)”. The questionnaire is in one clusters with 9 items.  The data collected were analyzed using Mean and Standard Deviation (SD) to answer the research question. The major findings of the study were that school principal’s negative attitude towards the budgetary plans, poor budget implementation, among others do actually affects budgeting practices of principals in administration of public secondary schools in Southwest, Nigeria. The finding also revealed that there is no statistically significant difference between the mean scores of the principals and bursars on principals’ budgeting practices in administration of public secondary schools in Southwest, Nigeria. Based on the findings of the study, it was recommended among others that Principals should endeavour to involve their staff in school budget planning and preparation and should not neglect their opinions and contributions for productive and effective administration of school.